1994
DOI: 10.2118/20259-pa
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery by Imbibition in Low-Permeability Chalk

Abstract: This paper describes experimental studies of spontaneous imbibition of oil by water in a low-permeability outcrop chalk. At constant and high interfacial tension (IFT), the importance of capillary forces and the existence of a predominantly countercurrent mechanism were established. Additional experiments were performed to investigate the influence of length and of various boundary conditions. In another investigation, we modified the IFT at the sample boundary by using pairs of conjugate phases of the n-hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 12 publications
(6 reference statements)
12
81
0
Order By: Relevance
“…Table 1 summarizes different forms of the viscosity term used in the literature. Lucas (1918), Gupta and Civan (1994), Behbahani and Blunt (2005), and Saboorian-Jooybari and Khademi (2014) used the wetting phase viscosity term in their equations and presented scaling groups similar to that of Mattax and Kyte (1962), whereas Iffly et al (1972), Cuiec et al (1994), Babadagli (1996), and Tavassoli et al (2005) used the nonwetting instead of the wetting phase viscosity. Ma et al (1997) experimentally observed that the imbibition time was proportional to the geometrical mean of wetting and nonwetting phase viscosities.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes different forms of the viscosity term used in the literature. Lucas (1918), Gupta and Civan (1994), Behbahani and Blunt (2005), and Saboorian-Jooybari and Khademi (2014) used the wetting phase viscosity term in their equations and presented scaling groups similar to that of Mattax and Kyte (1962), whereas Iffly et al (1972), Cuiec et al (1994), Babadagli (1996), and Tavassoli et al (2005) used the nonwetting instead of the wetting phase viscosity. Ma et al (1997) experimentally observed that the imbibition time was proportional to the geometrical mean of wetting and nonwetting phase viscosities.…”
Section: Discussionmentioning
confidence: 99%
“…In the static conditions, matrix properties such as matrix permeability and size 2) , wettability 3) , rock heterogeneity, matrix boundary conditions, fluid properties such as density and the chemical structure of water 4) , interfacial tension 5) and viscosity ratio have become known to be effective parameters on the capil lary imbibition.…”
Section: Major Parameters Of Capillary Imbibition Mechanism In Nfrsmentioning
confidence: 99%
“…The flow of the fluid in the cavity is free flow, and the flow of the fluid in the fractures and caves is described by the coupling of the seepage and the free flow. Discrete fracture cavity models [14][15][16] can reflect the development space of reservoirs, but it is highly dependent on the description technique of reservoirs. If considering the actual application and field staff training, the models do not have the advantages of application.…”
Section: Introductionmentioning
confidence: 99%